Corneal Biomechanical Changes after Crosslinking for Progressive Keratoconus with the Corneal Visualization Scheimpflug Technology. (22nd September 2014) - Steinberg, Johannes; Katz, Toam; Mousli, Aiham; Frings, Andreas; Casagrande, Maria K.; Druchkiv, Vasyl; Richard, Gisbert; Linke, Stephan J.
Abstract : Purpose. To evaluate the effect of corneal crosslinking in progressive keratoconus by applying in vivo corneal visualization Scheimpflug technology. Design. Longitudinal retrospective study. Subjects and Controls. Seventeen eyes of patients treated with corneal crosslinking for progressive keratoconus. Methods. Corneal visualization Scheimpflug technology analyses (research software version 6.07r08) of subjects with progressive keratoconus before and 3 months after corneal crosslinking (CXL) were reviewed retrospectively. t- test (for normal distribution) and Wilcoxon matched-pairs test (if not normally distributed) were used to test for statistically significant differences between pre- and post-CXL analyses. Results. We demonstrated statistically significant differences for the intraocular pressure (median: +3 mmHg, P = 0.004 ), the central corneal pachymetry (pachy; mean: −35 µ m, P < 0.001 ), the timespan between the air impulse release and the first applanation of the cornea (A1time; median: +0.12 ms, P < 0.05 ), and the timespan between the air impulse release and the second applanation of the cornea (A2time; median: −37 ms, P < 0.05 ). Conclusions. With the A1time and the A2time, we identified two parameters that demonstrated a statistically significant improvement of the biomechanical properties of the cornea after CXL. Despite the known initial decrease of the pachymetry after CXL, none of the analyzed parameters indicated a progression of the keratoconus.